Responsabilità penale e rischio nelle attività mediche e d'impresa (un dialogo con la giurisprudenza) Atti del convegno nazionale organizzato dalla Facoltà di Giurisprudenza e dal Dipartimento di Diritto comparato e penale dell'Università degli Studi di Firenze (7-8 maggio 2009) - BARTOLI, ROBERTO (Atti, 2010)
This book presents the proceedings of the conference held in Florence on 7 and 8 May 2009 upon the conclusion of a MUIR study. The inspiration behind it can be summarised in two keywords. The first is "modernity", because it focuses on the sectors of criminal liability of the doctor and the entrepreneur, those that have been most dramatically affected by social change and technological developments, straining to the limit the "classic" configuration of criminal law categories. The second is "case law", in the sense that we have sought to focus on the reality of living law and to investigate the concepts of the causality, blame and complicity of individuals as they are actually illustrated by precedents.